طريقة تحديد البنية انطلاقاً من الحركة كحل بديل لإنتاج الخرائط الصورية للمناطق الممتدة - الخليل عمر; فحصة إياد (Latakia University Journal -Engineering Sciences Series, 2019)
يهدف هذا البحث إلى إنتاج خارطة صورية على شكل موزاييك رقمي لجزء من مدينة اللاذقية. مدخلات هذه الخارطة هي مرئيات متداخلة ونقاط ضبط مقتطعة من المتصفح المجاني Google Earth. أما المعالجة فقد تمت بطريقتين، الأولى هي الطريقة التقليدية التي تقوم على إرجاع كل صورة لوحدها باستخدام نقاط الضبط ومن ثم تصنيع الموزاييك من الصور المرجعة باستخدام نظم المعلومات الجغرافية. أما الثانية فهي طريقة جديدة تعتمد على توجيه الصور باستخدام برمجيات قائمة على مبدأ "تحديد البنية انطلاقاً من الحركة" Structure from Mation (SfM) وتوليد موزاييك غير مضبوط منها ومن ثم ضبط هذا الموزاييك ضمن بيئة نظم المعلومات الجغرافية باستخدام نقاط الضبط. تم في البحث مقارنة الخارطتين الصوريتين الناتجتين من ناحية الدقة الهندسية حيث قمنا بمقارنة الخارطتين مع مخطط طبوغرافي أساسي (مقياسه 1/1000) للمنطقة المدروسة، كما ناقشنا مقاييس الخرائط المتجهية Vector maps الممكن توليدها من الخرائط الصورية الناتجة في كلتا الحالتين. أثبتت الدراسة أن النوعية الهندسية للخارطة الصورية أفضل عند تطبيق طريقة الـ SfM المؤتمتة والسريعة. The aim of this research is to produce a photomap in the form of a digital mosaic for a part of Latakia city. The inputs are a group of overlapping photos and control points, extracted from Google Earth. As for the processing, it was achieved in two manners. The first is a rectification-based method, where every image is rectified using control points and then the mosaic is produced from the rectified images using geographic information systems (GIS). The second is a new way of images orientation using Structure from Motion (SfM)-based software and then producing un uncontrolled mosaic. This mosaic is then georeferenced by using control points within GIS environment. In this study the two resulted photomaps were compared in terms of geometric accuracy. They were compared a base topographical map (scale of 1/1000) that represents the studied area. Also, the scales of vector maps that can be generated from the resulted photomaps in both cases, were discussed. The results showed that the geometric quality of the photomap in the case of automated and fast SfM is better.